Toward Algorithmic Due Process: Constitutional Challenges and Human Rights Risks in Indonesia’s Digital State - Syafri Hariansah; Laila Qhistina (Jurnal Pembangunan Hukum Indonesia, 2026)
The digital transformation of state governance has engendered a novel form of algorithmic authority that exerts a direct influence on human rights. In Indonesia, administrative determinations derived from digital systems, such as the Computer Assisted Test for civil service recruitment, the Integrated Social Welfare Database, digital identity applications, and inter-agency data integration facilitated by the One Data Indonesia initiative, are frequently executed without transparency, correction mechanisms, or accessible legal recourse. This scenario engenders a substantial disparity between the constitutional tenet of due process and the actualities of automated public decision-making. This scholarly inquiry endeavors to articulate the notion of algorithmic due process as a unique constitutional safeguard that transcends procedural fairness, administrative due process, and digital due process. Employing normative legal methodologies in conjunction with a socio-legal perspective, this research scrutinizes the Indonesian legal framework's responsiveness to the challenges engendered by algorithmic authority. The results indicate that Indonesia is deficient in adequate normative foundations to govern algorithmic justice and safeguard fundamental rights. Consequently, the study advocates for a model of algorithmic due process predicated on the rights to explanation, correction, and legal challenge, situated within the overarching theoretical paradigm of Rule of Law 5.0. The study underscores an imperative for constitutional reform to establish definitive standards for algorithmic governance in the realm of public services.